Application of Technology Acceptance Model on Electronic Book Design of Bandung City History Travel Guide - Eko Susanto; Melissa Shasya Bonita (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2022)
Historical tourism resources are one of the comparative and comparative advantages of Bandung city over other tourist destinations in Indonesia. The unique characteristic of historical tourism is that the power of narratives poses a broader need for means of interpretation in the form of travel guides. By applying the Technology Acceptance Model (TAM), this applied research reveals the process of designing electronic guidebooks that can aim to be used for the interpretation of historical tourism visitors in The City of Bandung. The design method with a descriptive writing pattern is used to produce research reports on the design of electronic guidebook products in Bandung. This applied study has gathered opinions from 132 respondents through questionnaires about the components of travel guidebooks following the Technology Acceptance Model (TAM) concept, which is then analyzed descriptively. This applied research has resulted in a travel guidebook product and an understanding that tourists require accessible travel guidebooks to use and value for themselves.